Interdisciplinary interactive blended learning concept in times of a pandemic - pain medicine "totally digital" - Schramm, Lisa; Friedrich, Patrick; Schüttler, Jürgen; Lütcke, Björn (GMS journal for medical education, 2022)
Pain medicine is located in different sections of the medical curriculum. In the pandemic situation, an online teaching concept for Q14 which includes several disciplines had to be developed. The goal of the project was to create a fully digitized learning platform for the cross-sectional area Q14 that allows all participating disciplines to address the various learning goals without losing a practical component. First, the students' expectations regarding education in the field of pain medicine were recorded by means of a survey among medical students. Based on this, a teaching module in a blended learning format was developed, which consisted of two parts. Within a digital learning platform, students were first required to complete consecutive learning units using an interactive learning management system. This was followed by a presence phase (online ZOOM seminar) in which, under the guidance of teaching staff, the therapy suggestions of the individual case studies from the previous learning program were reflected. In the second part, the acquired knowledge was applied to a simulated patient. An evaluation of the online module was carried out through free-text answers and self-assessment of the completion time. The ZOOM seminar was evaluated on the basis of an assessment by the teachers. The survey among students revealed a desire for practical training without "frontal teaching". The resulting project realized this aspect by teaching theory during an online module with case vignettes and interactive learning tasks. The subsequent online presence time during the ZOOM meeting enabled the students to repeat and deepen contents and to ask questions. 170 students completed the entire online program, of which evaluation data were available for 75 students. Self-assessment of completion time averaged at 4-6 hours. In the feedback, 90 aspects were addressed, including mainly comments on content (43%), praise (33%) and comments on technical problems (23%). According to the assessment of the presenters, the students were able to carry out the pain anamnesis survey in a structured manner. The submission of the therapy proposal, however, represents a particular hurdle. With the presented blended learning concept it is possible to address the different learning goals and the interdisciplinarity of Q14 sufficiently. After further processing and improvement of the project, a controlled and more extensive collection of evaluation data is required to further investigate the benefit of the platform for the students regarding achievement of defined learning goals.